Comparative study on the occurrence and severity of dry eyes between menopausal women not on hormone replacement therapy (HRT) and those on HRT in HUSM - Mokhtar, Saira Fairma Ismail (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Introduction: It is a known fact that Dry Eye Syndrome (DES) occurs more commonly in females of older age group compared to men. Menopausal women have lack of hormones that may contribute to dry eye. Hormone replacement therapy, therefore, is expected to prevent the occurrence of dry eye. However, this has never been scientifically proven. Objective: To investigate the occurrence and severity of Dry Eye in menopausal women in HUSM and to compare the results between women taking hormone replacement therapy and those not taking any hormone replacement therapy.Methodology: Menopausal women tn HUSM underwent eye examination consisting of the Schirmer's test, the tear film breakup time and the rose bengal staining. At least 2 of the tests need to be abnormal to diagnose dry eye. After the ocular examination, blood was taken from every patient for estradiol, progesterone and dehydroepiandrosterone sulfate levels.Results: Fifty-four women were examined, 30 (55.6°/o) of which were on honnone replacement therapy (HRT group), while 24 (44.4o/o) women were not on any honnone replacement therapy (control group). In the HRT group, 11 patients were on estrogen (Estrogen group) and 19 patients were on combined estrogen and progesterone (Combined group). Dry eye was found in 29.2% of patients in the control group and in 70.0% of patients in the HRT group [p<0.05]. Comparing the patients in the HRT group, dry eye occurred more frequently in the combined estrogen and progesterone group (84.2%) as compared to the estrogen only group (45.5%) [p<0.05]. When analysed separately, the only dry eye test found to be statistically significant was a positive BUT test between the Combined group (94.7%) and the Estrogen group (45.5°/o) [p<0.05]. The severity of dry eye was not statistically significant between groups. Conclusion: Dry eye was found more commonly in menopausal women who took hormone replacement therapy in Hospital Universiti Sains Malaysia. Combined estrogen and progesterone therapy was associated with a higher occurrence of dry eye compared to estrogen only therapy. These results, therefore, are in contrast to the previous assumption that HRT would prevent dry eye.